Analisis Literatur Fisika Nuklir Dan Pengembangan Reaktor Fusi - Selfin Putra Zega; Seven Hardiansyah Gulo (CV. SINAR HOWUHOWU, 2024)
This study presents a literature analysis on nuclear technology, focusing on the development of fusion reactors as a potential future energy source. Fusion reactors offer sustainable, safe, and environmentally friendly energy advantages over conventional fission reactors. However, the development of fusion reactors faces significant challenges, including plasma stability, high-temperature-resistant materials, and the need for strong magnetic fields to sustain fusion reactions. This literature review examines various approaches to addressing these challenges, including Tokamak and Stellarator technologies, the role of superconducting materials, and advancements in cooling systems and radioactive waste management. The study also highlights international efforts such as the ITER and DEMO projects as critical steps toward developing commercial fusion reactors. The analysis concludes that, despite technical and financial obstacles, technological advancements and global collaboration in fusion projects show promising potential for establishing fusion reactors as a reliable energy source in the future.